The institutional origins of state–society relations - Mohamed Ismail Sabry (Fulbright Review of Economics and Policy, 2022)
Purpose – This paper investigates the factors responsible for the emergence of different arrangements of state–society relations. Being concerned with the relations related to the industrial sector, this study focuses more on state–business–labor relations (SBLRs), especially on power dynamics between the main actors in these relations, namely, the state, tycoons, entrepreneurs and labor. Design/methodology/approach – Based on power dynamics, four SBLR modes are identified and differentiated according to state power vis-à-vis non-state actors and tycoon power vis-à-vis the other non-state actors. The balanced mode is characterized by balanced power relations among the four considered actors. In the capture mode, tycoons are more powerful than other actors, including the state, although other nonsocial actors have organizational rights. The crony mode has powerful state, subservient tycoons who enjoy high levels of favoritism and low organizational power for the other social actors. Finally, the state-dominance mode has powerful state, low levels of favoritism to tycoons and low organizational power for all social actors. The paper then explores the factors responsible for the emergence of each of these modes by investigating the factors’ effects on state power and favoritism to tycoons. The investigated factors include historical political–economic, geographical, legal and cultural factors. The hypothesized effects of these factors are then tested using a random-effects probit regression model, investigating how the different factors affect the probability of the existence of the studied SBLR modes. Findings – The results support much of the hypothesized relations and place more emphasis on some of the investigated factors. Earlier development is clearly responsible for the emergence of either the balanced or the state-capture SBLR mode. Geographical conditions favorable for development, such as latitude and metal richness, also lead to the emergence of either mode. The communist heritage, and more accurately the post-communist economic and incomplete political liberalism of the transition stage, contributed to the emergence of the state-capture SBLR mode. The British legal system, with the power it provides to non-state actors through the independence of judges and other measures, contributes to the emergence of the balanced SBLR mode. Cultural factors are largely responsible for the emergence of the crony SBLR mode, especially hierarchical and collectivist cultures, as well as ethnic fractionalization. On the other hand, the culture of Confucians has the strongest influence on the emergence of state dominance, while other cultures play a marginal role in its rise, and ethnic fractionalization marginally defuses the ability of the state to dominate without resorting to favoritism. Finally, access to rich natural resources, by enriching the state independently from social actors’ financial resources (e.g. taxation), marginally increases the probability of the emergence of the state-dominance mode. Research limitations/implications – There is room for path dependency to explain the emergence of different SBLR modes in many countries. Unfortunately, the introduced regression model and any quantitative empirical work would not be able to effectively investigate such a process. Instead, an approach depending on case studies and a deeper investigation of country-specific historical political development is needed to complement the research done here. Conducting such an additional quest would help in reaching a more comprehensive understanding of why different countries have different SBLR modes. This should ultimately help in answering an equally important question: How to reverse engineer the emergence of favorable SBLR modes? Practical implications – Although this paper did not investigate the economic merits or mischiefs of each of the studied modes, it is plausible to think of the balanced SBLR as the best mode. This is supported not only by the fact that most of the countries of this mode are developed countries but also by the attractiveness of the power dynamics governing this mode—a more balanced power among different SBLR actors. While some factors are almost impossible to replicate, for example, geographical factors, reform could target the factors that could be changed or mitigated. This is true for legal reform, especially for fostering the independence of judges. Culture is often regarded as a sticky institution. However, this is not always true, even though the change happens in the long run. A sort of dynamism should always be considered when referring to culture through time and space. Institutional reform could be instrumental in the long run in this regard. Conducting such reform with the help of such “exogenous” institutions should always consider the match between these institutions and “endogenous” institutions, such as culture. That is to say, the connection between democratization, fostering accountability and curbing favoritism and cultural values leaning toward these principles should be firmly established. Finally, a point of optimism is that—based on the results of this paper—reaching a high state of development could increase the chances of realizing a more balanced SBLR mode in the long run. Originality/value – This paper represents a novel contribution to a topic that has hardly been addressed in the literature. The methodology that is used identifies different state–society relation modes and focuses on power relations in SBLRs is another important contribution to the present literature in many fields, such as institutional economics, socioeconomics and political economy.